Cocoa: Innovation, productivity and application in goat dairy products (Research, Society and Development, 2024)
Cocoa is one of the most important agricultural products in the world, it has a well-established production chain and Brazil is one of the largest producers in the world. It is considered a viable raw material for the production of functional foods, due to its high levels of bioactive substances and antioxidants. Therefore, the study aims to conceptualize cocoa in terms of origin, productivity, impact on health, innovation in the food industry, in addition to the feasibility of its application in goat dairy products through an bibliographic review. The methodological approach allowed the use of experimental and non-experimental studies to have a complete understanding of the proposed theme. The search was carried out on the basis of ScienceDirect, Scielo, Web of Science, SCOPUS and Schollar Google and was restricted to open access studies published from 2019 to 2023 using “cocoa”, “healthy”, “dairy”, “goat milk” as words -key. Through the study, it was possible to analyze the cocoa production chain in terms of the world scenario, understanding that despite the covid-19 pandemic, cocoa remains relevant, promising and in demand in the market. Using it as a basis, it is possible to develop a range of products with a high content of bioactive compounds, thus bringing benefits to the health of the consumer. It can also be seen the feasibility of adding cocoa associated with other probiotic and prebiotic substances in goat dairy products, thus resulting in products accessible to society with satisfactory nutritional and sensory characteristics.